PENGARUH CAPITAL ADEQUACY RATIO, LOAN TO DEPOSIT RATIO, NON PERFORMING LOAN, DAN BEBAN OPERASIONAL PENDAPATAN OPERASIONAL TERHADAP RETURN ON ASSET (STUDI EMPIRIS PADA SEKTOR PERBANKAN KONVENSIONAL YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2019-2023) - Alvyanti, Prilcyana; Laksmiwati, Mia (LPPM Universitas Bina Bangsa, 2025)
This research aims to determine the significant influence of the variables Capital Adequacy Ratio, Loan To Deposit Ratio, Non Performing Loan, Operating Costs and Operating Income on Return On Asset. The data used is secondary data in the form of annual financial reports of conventional banking sector companies listed on the Indonesia Stock Exchange period 2019-2023. The sample selection in this study used a purposive sampling method, as many as 10 companies from 43 conventional banking sector companies listed on the Indonesia Stock Exchange period 2019- 2023. The analytical tool used is multiple linear regression which was tested using the SPSS version 26 program with the stepwise method. The results of this research show that the Capital Adequacy Ratio has no effect on Return On Asset. Loan To Deposit Ratio has a positive and significant effect onReturn On Asset. Non Performing Loan and Operating Costs Operating Income have a negative and significant effect on Return On Asset.